Improvement of Complexity and Performance of Least Square Based Channel Estimation in MIMO System - Sah, Anand Kumar; Timalsina, Arun Kumar (Journal of Advanced College of Engineering and Management, 2016)
Multiple-input multiple-output (MIMO) systems play a vital role in fourth generation wireless systems to provide advanced data rate. In this paper, a better performance and reduced complexity channel estimation method is proposed for MIMO systems based on matrix factorization. This technique is applied on training based least squares (LS) channel estimation using STBC for performance improvement. Simulation results indicate that the proposed method not only alleviates the performance of MIMO channel estimation but also significantly reduces the complexity caused by matrix inversion. The performance evaluations are validated through computer simulations using MATLAB in terms of bit error rate (BER) for modified LS with LS and MMSE channel estimation techniques. Simulation results show that the BER performance and complexity of the proposed method clearly outperforms the conventional LS channel estimation method. Journal of Advanced College of Engineering and Management, Vol. 1, 2015, pp. 11-24